PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN MOUTHWASH LISTERINE PT ALVA KARYA PERKASA (Studi Kasus Supermarket Area Bogor) - Purwanti; Agustiani, Desi (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of price and product quality on customer satisfaction in PT. Alva Karya Perkasa (Bogor area supermarket case study). The research method used is quantitative. The population in this study was all customers of Listerin Mouthwash products using a saturated sample of 100 respondents from 32 store.The data analysis method uses simple linear regression tests, multiple linear regression, correlation coefficients, determination coefficients, partial t tests and simultaneous F tests. The results of the multiple linear test obtained the equation Y = 3.637 + 0.109X1 + 0.441X2, show that there is a positive and significant influence of price (X1) and product quality (X2) on customer satisfaction (Y).The value of the correlation coefficient obtained at 0.837 is in the interval 0.80-1.00, meaning that the variables price (X1) and product quality (X2) have a very strong level of relationship to customer satisfaction (Y). The value of the R square coefficient of determination of 0.700 means that the price and product quality variables simululatively contribute to the customer satisfaction variable by 70%, the remaining 30% is influenced by other variables that are not studied.Based on the T test, the calculated value of ttable > (2.523 > 1.984) and sig 0.03 (0.04 < 0.05) means that there is an effect of price on customer satisfaction. Based on the T test, the calculated value of ttable > (2.615 > 1.984) and sig 0.00 (0.00 < 0.05) means that there is an influence of product quality on customer satisfaction. The F test results obtained Fcalculate > Ftable values (113.270 > 3.09) and sig 0.000 (0.00 < 0.05) meaning that there is an influence of price and product quality on customer satisfaction in PT. Alva Mighty Works.